PERANAN ANGGOTA KELOMPOK TANI DALAM MENINGKATKAN PRODUKSI PADI SAWAH DI DESA KOROBHERA KECAMATAN MEGGO KABUPATEN SIKKA - Toncerius M. Lesu; S.P.N. Nainiti; Serman Nikolaus (Buletin Ilmiah Impas, 2020)
The aim of this research is to find out how big the role of the farmer group members in increasing rice production at Korobhera Village, Meggo Subdistrict, Sikka District. The research has been done on April to May 2019. This is a qualitative study with purposive sampling considering the site was one of rice central production. The objectives of the study were to know : 1) how big the role of the farmer group members to productivity increasing in the area of research ; 2) the constraints faced by the members of the farmer group. Sample was done randomly using simple random sampling method with a total sample size of 50 people, who were the members of four farmer groups existed. The results of research indicated that the role of farmer group members in increasing rice production at the location of research was high, shown by the percentage of the accomplishment maximum score from average score in the amount of 75,65% (average score 87). The constraints faced by members of farmer group were quite similar, which were financial capital limits problem, uncaged livestocks and the availability of production tools was often not on time.